Based on the successful piloting of bundled risk solutions in three South Asian countries, new indexed crop insurance and technology practices are being scaled out by governments and insurance companies , benefitting thousands of farmers - CGIAR Research Program on Water, Land and Ecosystems (2021)
In South Asia, the CGIAR-led innovation of bundled agricultural technologies (including index-based flood insurance, climate resilient seeds and agroclimatic services), relying on advanced tools and modeling including satellite data, speeded payouts to over 15,000 flood-affected farm households, indirectly benefitting another 125,000 farmers who learned from participating neighbors. Governments and insurance companies are beginning to scale out these new products to farmers, including women, in Bangladesh, India and Sri Lanka. Over time, these innovations will have long-term impacts on resilient development.